2007
DOI: 10.1016/j.febslet.2007.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Managing and exploiting stress in the antibody factory

Abstract: Like us, our cells have evolved strategies to cope with, and sometimes utilize, stress. Molecular analyses of plasma cell biogenesis, lifestyle and death suggest that protein synthesisdependent stress is utilised to integrate differentiation, function and lifespan control. Plasma cells are short-lived professional secretory cells, each of them capable of releasing several thousands antibodies per second. Their differentiation from B lymphocytes entails the spectacular enlargement of the endoplasmic reticulum (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
87
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(92 citation statements)
references
References 67 publications
4
87
1
Order By: Relevance
“…8) Translation is sensitive to redox conditions through Trx interactions and Trx-like domains in elongation initiation factors. 9) Processing of proteins destined for secretion or insertion in the plasma membrane, such as VCAM-1, ICAM-1, and E-selectin often require redox-dependent processing in the secretory pathway (7,24). 10) Function of cell surface receptors is dependent on redox-sensitive Cys in integrins, cytoskeletal proteins (e.g., actin, cofilins), and Cys-rich regions in the receptors.…”
Section: Steady-state E H Of Cys Residues In Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…8) Translation is sensitive to redox conditions through Trx interactions and Trx-like domains in elongation initiation factors. 9) Processing of proteins destined for secretion or insertion in the plasma membrane, such as VCAM-1, ICAM-1, and E-selectin often require redox-dependent processing in the secretory pathway (7,24). 10) Function of cell surface receptors is dependent on redox-sensitive Cys in integrins, cytoskeletal proteins (e.g., actin, cofilins), and Cys-rich regions in the receptors.…”
Section: Steady-state E H Of Cys Residues In Proteinsmentioning
confidence: 99%
“…Sites sensitive to changes in thiol-disulfide redox state are indicated by an "-SH/-SS-" balance. A: in early proinflammatory signaling in endothelial cells, redox-dependent signaling includes 1) extracellular Cys/CySS redox potential (55) (109); 9) processing of proteins in the secretory pathway (7,24); and 10) cytoskeletal/ surface structure (33,140,187). B: in receptormediated signaling, redox-sensitive steps include 1) metalloprotease-sensitive growth factor release (134); 2) metalloprotease-sensitive degradation of growth factor inhibitor (51); 3) redox-dependent activation of receptors (31, 94); 4) H2O2-dependent Ca 2ϩ influx and Nox-5 activation (40); 5) active-site Cys residues required for phosphatase activity [PTP1B, SHP2, PTen; (39)]; 6) Ras activity (3); 7) Src activity (48); 8) H2O2 metabolism; 9) lipoxygenase activity (42); 10) LPS activation of cytoplasmic and mitochondrial H2O2 production through Toll-like receptor 4 [TLR4 (77,139)] (42,77,139).…”
Section: Oxidative Stress As a Disruption Of Redox Signaling And Controlmentioning
confidence: 99%
“…Multiple myeloma cells are characterised by expanded ER (Cenci and Sitia, 2007). Misfolded proteins in the ER are directed to the proteasome for degradation (ER-associated degradation -ERAD) (Ding et al, 2007).…”
mentioning
confidence: 99%
“…23 As plasma cells are subjected to ER stress when excess amount of proteins are synthesized, 14 there is a possibility that ABCG2 expression might be enhanced in the plasma cells that are subjected to ER stress under IL-6-rich situation. In fact, IL-6 and ER stress inducers, tunicamycin, thapsigargin and 2-deoxyglucose, synergistically increased the level of ABCG2 expression in RPMI8226 and U266 plasma cells.…”
Section: Discussionmentioning
confidence: 99%
“…We found significantly strong ABCG2 expression in a small proportion of plasma cells, which are known to be under the endoplasmic reticulum (ER)-stressed condition for synthesis of a large amount of proteins. 14 It is reported that hypoxia induces increase of ABCG2 expression level, 15 but effect of ER stress on ABCG2 expression remains unclear. We hypothesized that a small population of plasma cells might express high level of ABCG2 under severe ER stress.…”
mentioning
confidence: 99%